2018
DOI: 10.1186/s12891-018-2176-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of aneurysmal bone cysts using endoscopic curettage

Abstract: BackgroundAlthough aneurysmal bone cysts (ABCs) are benign tumours, they have the potential to be locally aggressive. Various treatment approaches, such as en bloc resection, open curettage, radiotherapy, sclerotherapy, and embolization have been proposed, but the most appropriate treatment should be selected after considering the risk of tumour recurrence and treatment complications. Endoscopic curettage (ESC) may be a less invasive alternative to open curettage for ABC treatment. We aimed to describe the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 33 publications
1
23
2
1
Order By: Relevance
“… 11 , 17 , 18 , 31 , 33 , 36 , 38 , 39 Two studies of minimally invasive curettage techniques, without adjuvant therapy or grafting, reported treatment failures or recurrence in 40% (12/30) and 22% (2/9) of cases. 30 , 32 One study evaluated open biopsy with application of a paste composed of demineralized bone and bone marrow aspirate, without any formal curettage; 24% (5/21) of patients failed to heal at a mean follow-up of 53 (24 to 106) months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 17 , 18 , 31 , 33 , 36 , 38 , 39 Two studies of minimally invasive curettage techniques, without adjuvant therapy or grafting, reported treatment failures or recurrence in 40% (12/30) and 22% (2/9) of cases. 30 , 32 One study evaluated open biopsy with application of a paste composed of demineralized bone and bone marrow aspirate, without any formal curettage; 24% (5/21) of patients failed to heal at a mean follow-up of 53 (24 to 106) months.…”
Section: Resultsmentioning
confidence: 99%
“… 48 Since publication of the included studies, Ethibloc has been withdrawn from commercial use. Factors associated with treatment success or failure were examined in several studies, which identified younger age of presentation, 17 , 31 , 32 , 37 involvement of the physis, 32 , 37 and previous treatment (recurrent cysts) 31 to be negative prognostic indicators. Pathological fracture was not investigated as a potential prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, direct visualization avoids blind spots or excessive curettage, which may result in intraoperative fracture or cartilage damage. Recently, in a retrospective study, Aiba et al [27] reported the use of MIET to treat 30 patients with aneurysmal bone cysts (ABCs). Good postoperative functional recovery was achieved in all patients following the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another distinct advantage of MIET is that it provides an excellent opportunity for trainees and medical students to observe every step of the operation on a video screen, which is especially beneficial for expansion of this technique into the field of orthopedic oncology. Although limited evidence is available, some studies have shown that the MIET produces an excellent profile of efficacy for the treatment of benign bone tumors, such as giant cell tumors of the tendon sheath, simple bone cysts, aneurysmal bone cysts and chondroblastomas [24] , [25] , [26] , [27] , [28] , [29] , [30] . In China, however, few studies have evaluated this therapeutic modality, with most studies published to date comprising case reports that do not report comprehensive outcome measures (including VAS, MSTS and SF-36 scores) [31] .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Aiba et al . [53] suggested endoscopic curettage as a minimally invasive method for treating aneurysmal bone cysts with a recurrence rate of 10%, which is comparable to that of other procedures. Other treatment approaches, such as application of methylprednisolone acetate, bone allografts, and insertion of gelfoam saturated with penicillin and thrombin are also tried [54].…”
Section: Discussionmentioning
confidence: 99%